Nucleoporins shape germ granule architecture and balance small RNA silencing pathways - Kun Shi; Ying Zhang; Zhenzhen Du; Symonne C. Liu; Ivan Leon; Xinyu Fan; Heng-Chi Lee; Donglei Zhang (Nature Communications)
Abstract Animals use small RNA pathways, such as PIWI-interacting RNA (piRNA) and small interfering RNA (siRNA), to silence harmful genetic elements. In Caenorhabditis elegans, piRNA pathway components are organized into sub-compartments within germ granules near nuclear pore complexes, but the basis and function of this association have remained unclear. Here, our data suggest that germ granule formation and nuclear pore clustering are interdependent processes. We identify the conserved nucleoporins NPP-14/NUP214 and NPP-24/NUP88, along with the germ granule protein EPS-1, as key factors anchoring germ granules to nuclear pores. Loss of these factors leads to disorganized, fused granules and enhanced piRNA silencing. Artificial tethering of granule sub-compartments mimics this effect. However, this increase in piRNA silencing comes at the expense of RNA interference efficiency and heritability. Our findings reveal the molecular factors mediating germ granule–nuclear pore interaction and highlight how spatial organization of RNA silencing machinery fine-tunes gene regulation.